Legal Approaches to Climate Change Mitigation: Evaluating Implementation Strategies and Mainstreaming Efforts - Yusdiyanto, Yusdiyanto; Budiyono, Budiyono; Saleh, Ahmad; Nurhalimah, Dewi; Gultom, Rachel Sophia Joy Aprilia (Fakultas Hukum Universitas Lampung, 2024)
Climate change poses a serious threat to all nations. According to the World Economic Forum's Global Risk Report (2019), climate change ranks among the most significant global risks, contributing to natural disasters, extreme weather events, food and water crises, biodiversity loss, and ecosystem collapse. These impacts have profound consequences for human life. Despite growing awareness of climate change as a critical issue, large-scale efforts to mitigate its effects remain insufficient. This research seeks to analyze the factors contributing to the lack of public awareness in addressing climate change, particularly from a legal perspective. Legal frameworks play a crucial role in mainstreaming climate change mitigation and adaptation to prevent environmental disasters and promote sustainable development. Employing a normative approach, this research will explore the legal mechanisms necessary for integrating climate change mitigation and adaptation into regulatory frameworks.